Identifikasi Kesesuaian Potensi Ekowisata Di Desa Jatiluwih Kecamatan Penebel Kabupaten Tabanan Dengan Prinsip Ekowisata - Jaya, I Made Anom Krisna; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p20, 2018)
Jatiluwih tourist attraction have a big opportunity to be an ecotourism object. Ecotourism can mix both between natural and cultural conservation with local participation. So important to do a research on the potential of ecotourism in the village and to the principle of ecotourism. Data colectiom technique by observation, interviews and study literature. Technique the determination of informants by purposive sampling. Technique data analysis in this research by Miles and Huberman models. Jatiluwih Village have natural and cultural potential. Based on nine ecotourism principle and criteria, Jatiluwih Village have met six ecotourism principle and criteria. The idela ecotourism development can be done by fulfillment of three other ecotorousim principle and criteria.   Keywords : ecotourism, potential, principle